Penetapan Dana Desa Sebagai Force Majeure Dalam Penanganan Corona Virus Disease 2019 Di Desa Gemawang Tahun 2020-2022 - Supriyono Supriyono; Nanik Sutarni; Adhiputro Pangarso Wicaksono (Jurnal Bedah Hukum, 2022)
DETERMINATION OF VILLAGE FUND AS A FORCE MAJEUR IN HANDLING CORONA VIRUS DISEASE 2019 IN GEMAWANG VILLAGE 2020-2022 Gemawang Village is one of the villages in Jambu District, Semarang Regency which implements Law Number 6 of 2014 concerning Villages, but in determining the different 2019 Corona Virus Disease handling budgets in 2020-2022 which is mandatory in the budget, it requires a sufficient process. long considering that the determination of the budget has been determined in the previous year. Some of the problems that arise as a result of the Corona Virus Disease 2019 pandemic require several problem formulations in completing the budget changes that have been set, so that everything can be carried out in accordance with the government's expectations but does not leave the basis for determining the deliberation set by the village and approved by the Village Consultative Body. The purpose of this study was to find out about village procedures in force majeure in determining the budget for handling Corona Virus Disease 2019 in Gemawang Village in 2020 to 2022 based on Law Number 6 of 2014 concerning Villages. In Gemawang Village, Jambu District, Semarang Regency, this research uses an empirical juridical approach which examines the process of determining the budget process for determining the 2019 Corona Virus Disease Handling Budget in Gemawang Village, Jambu District, Semarang Regency. Some of the benefits for the author in compiling this thesis, one of which is to fulfill the requirements for a Bachelor of Law, knowing the process in determining the Corona Virus Disease 2019 budget in Gemawang Village, as a legal research study on Force Majeure in Determining the 2019 Corona Virus Disease Management Budget in Gemawang Village. The results of the research on the determination of the Village Fund as a Force Majeur in Handling Corona Virus Disease 2019 in Gemawang Village in 2020 - 2022, are in accordance with Law No. 6 of 2014 concerning Villages, Ministerial Regulations and Presidential Regulations, this proves that the Gemawang Village Government has implemented regulations set by the government to protect citizens from the spread of covid-19 with a budget sourced from the Village Fund for handling Corona Virus Disease 2019 in Gemawang Village, in a state of force (force majeure) as a non-natural disaster determined by the central government which has an impact on the determination a budget managed by the village sourced from the State Revenue and Expenditure Budget. PENETAPAN DANA DESA SEBAGAI FORCE MAJEUR DALAM PENANGANAN CORONA VIRUS DISEASE 2019 DI DESA GEMAWANG TAHUN 2020-2022 Desa Gemawang adalah salah satu Desa di Kecamatan Jambu Kabupaten Semarang yang melaksanakan Undang-Undang Nomor 6 Tahun 2014 tentang Desa, namun dalam penetapan anggaran penangganan Corona Virus Disease 2019 yang berbeda-beda pada tahun 2020-2022 yang wajib di anggaran, membutuhkan proses yang cukup panjang mengingat bahwa penetapan anggaran sudah di tetapkan ditahun sebelumnya. Beberapa permasalahan yang timbul dari akibat pendemi Corona Virus Disease 2019 dibutuhkan beberapa rumusan masalah dalam menyelesaikan perubahan anggaran yang sudah ditetapkan, agar semua dapat terlaksana sesuai dengan harapan pemerintah namun tidak meninggalkan dasar penetapan musyawarah yang ditetapkan desa dan disetujui oleh Badan Permusyawaratan Desa. Tujuan penelitian ini untuk mengetahui tentang tata cara desa dalam force majeure dalam menetapkan anggaran penanganan Corona Virus Disease 2019 di Desa Gemawang di tahun 2020 sampai dengan Tahun 2022 berdasarkan Undang-undang Nomor 6 Tahun 2014 Tentang Desa. Di Desa Gemawang Kecamatan Jambu Kabupaten Semarang penelitian ini adalah menggunakan pendekatan yuridis empiris di mana mengkaji proses proses penetapan anggaran penetapan Anggaran Penanganan Corona Virus Disease 2019 di Desa Gemawang Kecamatan Jambu Kabupaten Semarang. Beberapa manfaat penulis dalam menyusun skripsi ini, salah satunya untuk memenuhi syarat Sarjana Hukum, mengetahui proses dalam penetapan anggaran penangganan Corona Virus Disease 2019 di Desa Gemawang, sebagai kajian penelitian hukum tentang Force Majeure dalam Penetapan Anggaran Penangganan Corona Virus Disease 2019 di Desa Gemawang. Hasil Penelitian Penetapan Dana Desa Sebagai Force Majeur Dalam Penanganan Corona Virus Disease 2019 Di Desa Gemawang Tahun 2020 - 2022, sudah sesuai dengan Undang-Undang No 6 Tahun 2014 Tentang Desa, Peraturan Menteri dan Peraturan Presiden , Hal ini membuktikan bahwa Pemeritah Desa Gemawang telah melaksanakan peraturan yang ditetapkan oleh pemerintah untuk melindungi warga masyarakat dari penyebaran covid-19 dengan anggaran yang bersumber dari Dana Desa untuk penanganan Corona Virus Disease 2019 Desa Gemawang, dalam keadaan memaksa ( force majeure ) sebagai bencana non alam yang ditetapkan oleh pemerintah pusat yang berdampak pada penetapan anggaran yang dikelola oleh desa yang bersumber dari Anggaran Pendapatan Dan Belanja Negara.